Detection and imaging of ground targets based on new approaches in radar imaging implementation in SOC technology - Salma Fatima, Syeda; Madathil, Deepa (International Journal of Engineering and Technology, 2018)
SAR system collects the image by sending signals on to the ground and collecting the reflected signals from the stationary target that is present on the ground. Here we have used Doppler Algorithm, by continuously moving the antenna in order to get clear resolution. This paper presents simulation for 2D rectangular shaped targets that are present on the ground. We have given two-dimensional, grayscale target image as an input to perform simulation and we obtain a two-dimensional line profile with the help of reflected signals.Â